Tight Non-Radiating Bends of 3D-Printed Dielectric Image Lines Based on Electromagnetic Bandgap Mirrors - Hahn, Leonhard; Bader, Tobias; Carlowitz, Christian; Vossiek, Martin; Gold, Gerald (2024 IEEE Wireless and Microwave Technology Conference (WAMICON), 2024)
This paper reports on a novel compact, low-loss bending technique for additively manufactured dielectric image lines between 140 GHz and 220 GHz. Conventional bending approaches require either large curvature radii or technologically challenging permittivity variations to prevent radiation loss at line discontinuities, e.g. caused by narrow bends. In contrast, this work uses extremely compact, easy-to-manufacture electromagnetic bandgap (EBG) cells to solve the afore mentioned challenge for the first time. These offer excellent reflection properties and thus enable broadband and low-loss (IL < 1 dB) guidance of electromagnetic waves by means of total reflection. Without increasing the complexity of the process, both the high-pass behaviour and the enormous space requirement of conventional dielectric bends are completely avoided. In addition, the use of EBGs improves the mutual isolation of dielectric image lines of up to 30 dB. Therefore, a promising solution for the realization of narrow, 3D-printed, low-loss signal distribution networks in the sub-THz domain is offered.<br
Keywords: Wireless communication; Microwave technology; Bending; Reflection; Metamaterials; Dielectrics; Mirrors; Dielectric image lines; electromagnetic bandgap; 3D-printing; low-loss; bending structures; sub-THz